Privacy and identity management : data for better living : 14th IFIP WG 9. 2, 9. 6/11. 7, 11. 6/SIG 9. 2. 2 International Summer School, Windisch, Switzerland, August 19-23, 2019, Revised Selected Papers /: data for better living : 14th IFIP WG 9. 2, 9. 6/11. 7, 11. 6/SIG 9. 2. 2 International Summer School, Windisch, Switzerland, August 19-23, 2019, Revised Selected Papers. (2020) - Unknown
No abstract available